2021
DOI: 10.1177/1479973121994781
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of physical activity in people with COPD: predicting physical activity after pulmonary rehabilitation using an integrative competence model

Abstract: The integrative Physical Activity-related Health Competence (PAHCO) model specifies competences (movement competence, control competence, and self-regulation competence) that enable people to lead a physically active lifestyle. This longitudinal study analyses the predictive quality of a multidimensional PAHCO assessment for levels of physical activity (PA) and their relevance for quality of life in COPD patients after pulmonary rehabilitation. At the end of an inpatient pulmonary rehabilitation (T2), 350 COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(78 reference statements)
2
15
1
Order By: Relevance
“…Alongside this person-oriented study, our ndings are partly in agreement with the results of a longitudinal study on PAHCO in chronic obstructive pulmonary patients, which found a positive, bivariate relationship between the subscales of PAAR and PASR after a rehabilitation program and the PA level six months after the program (70). In addition, this study also found a positive, bivariate relationship between the subscales of PASR, PAAR and CCPT after the rehabilitation program and the patients' quality of life after six months.…”
Section: Analysing the Changeability And Temporal Stability Of Pahcosupporting
confidence: 90%
See 1 more Smart Citation
“…Alongside this person-oriented study, our ndings are partly in agreement with the results of a longitudinal study on PAHCO in chronic obstructive pulmonary patients, which found a positive, bivariate relationship between the subscales of PAAR and PASR after a rehabilitation program and the PA level six months after the program (70). In addition, this study also found a positive, bivariate relationship between the subscales of PASR, PAAR and CCPT after the rehabilitation program and the patients' quality of life after six months.…”
Section: Analysing the Changeability And Temporal Stability Of Pahcosupporting
confidence: 90%
“…However, the ndings regarding the effect of PAHCO on HEPA and HRQOL remain tentative, as most of the research on this model has been cross-sectional (20,37,38,32,34,31) with only few studies employing a longitudinal design in adult populations (40,39). Alongside this, two interventional studies (41,42) yielded initial results concerning the changeability of this model in secondary school students showing improvements in PAHCO.…”
Section: State Of Research On Pahco Hrqol and Hepamentioning
confidence: 99%
“…First, quality of life plays a prominent role for patients with COPD, and second, we were able to show in a previous analysis of the STAR data that quality of life is directly related to physical activity. 42 The descriptive effects of the pedometer-based intervention on quality of life were even smaller and statistically insignificant. However, the improvement in both groups (IG and CG) indicates a positive effect of the PR program here as well.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, the STAR study encompasses a combination of physical, psychological, and behavioral assessments, allowing to complement the quadrant concept with further behavioral aspects of PA. In line with the criteria defined in the main analyses of STAR [ 27 , 28 ], the present study included all participants who (a) provided informed consent to participate in the study, (b) were granted inpatient rehabilitation at Bad Reichenhall Clinic, Germany, (c) actually attended pulmonary rehabilitation (PR), and (d) whose COPD diagnosis was confirmed by a lung function test (Tiffeneau index FEV1/VC ≤ 0.70) that was performed at the beginning of the PR (T1). In line with the analytical strategy of the present article, participants (e) had to provide valid accelerometry-measured PA data at T0 and valid PC data at T1.…”
Section: Methodsmentioning
confidence: 99%